2018
DOI: 10.1080/14999013.2017.1405124
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Needs of Long-Stay Forensic Psychiatric Inpatients: A Rapid Review of the Literature

Abstract: This rapid review summarises currently available information on the definition, prevalence, characteristics and needs of long-stay patients within forensic psychiatric settings.Sixty nine documents from 14 countries were identified. Reports on what constitutes 'long-stay' and on the characteristics of long-stay patients were inconsistent. Factors most frequently associated with longer stay were seriousness of index offence, history of psychiatric treatment; cognitive deficit, severity of illness, diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(36 citation statements)
references
References 82 publications
(58 reference statements)
1
33
0
Order By: Relevance
“…Due to their backgrounds, namely their offending histories, MDOs are often cared for in secure environments, either in prison or in dedicated forensic-psychiatric hospitals. These institutions are high cost-low volume services that may detain their clientele for long periods of time in highly restrictive conditions (for a review of length of stay in forensic psychiatric institutions see [16]). The purpose of this detention is seen as twofold: care and treatment for the patient (for their own sake as well as in order to reduce future risk) and protection of the public from harm from the offender.…”
Section: Forensic Psychiatrymentioning
confidence: 99%
“…Due to their backgrounds, namely their offending histories, MDOs are often cared for in secure environments, either in prison or in dedicated forensic-psychiatric hospitals. These institutions are high cost-low volume services that may detain their clientele for long periods of time in highly restrictive conditions (for a review of length of stay in forensic psychiatric institutions see [16]). The purpose of this detention is seen as twofold: care and treatment for the patient (for their own sake as well as in order to reduce future risk) and protection of the public from harm from the offender.…”
Section: Forensic Psychiatrymentioning
confidence: 99%
“…Reasons for delayed discharge are likely to include poor response to treatment, ongoing safety issues, and lack of a suitable stepdown facility. A recent review found the factors most frequently associated with longer stay included seriousness of the index offence, history of psychiatric treatment, cognitive deficit, severity of illness, diagnosis of a psychotic disorder and history of violence [18]. Whereas qualitative studies have shown, for example, that forensic patients can appreciate the therapeutic benefit of having a 'safe space' in order to progress [24], there is little information on how long stay patients view the reasons for their long stay in secure settings or how they feel about possible progression through the system, perhaps to a lower level of security or even to discharge to the community.…”
Section: Introductionmentioning
confidence: 99%
“…There are, to our knowledge, no earlier studies specifically investigating this issue, although a number of studies have identified overrepresentation of people from Black and Ethnic Minority groups among those detained under mental health legislation more generally as well as in high and medium secure services in the United Kingdom. On the other hand, a review of studies of 38 publications on long‐stay patients in forensic hospital settings (Huband et al, ), found that being black was associated with shorter length of stay in hospital, so we might have expected to find underrepresentation among people who stay for long periods in secure settings. The issue is likely to be confounded by other factors.…”
Section: Discussionmentioning
confidence: 94%
“…The finding that NHS long-stay patients were more ethnically diverse warrants further discussion. There are, to our knowledge, no earlier studies specifically investigating this issue, although a number of studies have identified (Huband et al, 2018), found that being black was associated with shorter length of stay in hospital, so we might have expected to find underrepresentation among people who stay for long periods in secure settings. The issue is likely to be confounded by other factors.…”
Section: Discussionmentioning
confidence: 95%